The Unholy Trinity: Childhood Trauma, Adulthood Anxiety, and Long-Term Pain - Kascakova, Natalia; Furstova, Jana; Hasto, Jozef; Madarasova Geckova, Andrea; Tavel, Peter (International journal of environmental research and public health, 2020)
BACKGROUND: Childhood trauma is considered to be a risk factor for developing anxiety as well as chronic pain. The aim of this study was to assess the association between childhood trauma and reporting anxiety and long-term pain conditions in the general and clinical populations. METHODS: Respondents from a representative sample in the Czech Republic (n = 1800, mean age: 46.6 years, 48.7% male) and patients with a clinically diagnosed anxiety or adjustment disorder (n = 67, mean age: 40.5 years, 18.0% male) were asked to report anxiety, various chronic and pain-related conditions, and childhood trauma (The Childhood Trauma Questionnaire, CTQ) in a cross-sectional questionnaire-based survey conducted in 2016 and 2017. RESULTS: Reporting emotional abuse (Odds ratio OR from 2.14 to 14.71), emotional neglect (OR from 2.42 to 10.99), or physical neglect (OR from 2.24 to 3.30) was associated with reporting anxiety and long-term pain both in the general and clinical populations and reporting physical abuse moreover with reporting anxiety or adjustment disorder with concurrent long-term pain (OR from 4.04 to 6.39). CONCLUSION: This study highlights the relevance of childhood trauma as a possible factor contributing to anxiety with concurrent pain conditions in adulthood in both the general and clinical populations.
Keywords: Young Adult; Cross-Sectional Studies; Male; anxiety disorder; Risk Factors; chronická bolest; mladý dospělý; Česká republika; Child; Child Abuse; chronic pain condition; dítě; Adult; dospělí; mužské pohlaví; Chronic Pain; průzkumy a dotazníky; adulthood anxiety; Czech Republic; clinical sample; úzkost; childhood trauma; lidé; ženské pohlaví; Humans; community sample; rizikové faktory; průřezové studie; zneužívané dítě; Female; Surveys and Questionnaires; lidé středního věku; Anxiety; Middle Aged